Hubungan Mindset dengan Self-Efficacy Pada Mahasiswa Magang di Ruang Belajar Aqil - Muhammad Irpansah; Frischa Meivilona Yendi; Yeni Karneli; Dina Sukma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study examines the relationship between mindset and self-efficacy among student interns at Ruang Belajar Aqil using a quantitative correlational approach. Data were collected through questionnaires from purposively selected student interns. The instruments used consisted of a mindset questionnaire developed by the researcher based on mindset indicators and a self-efficacy questionnaire. Data were analyzed using a Pearson correlation test. The results showed a positive and significant relationship between growth mindset and self-efficacy. This finding provides important insight into the role of mindset in shaping students' self-confidence during their internship assignments. Students with a growth mindset tend to have a high level of self-efficacy in completing tasks, overcoming challenges, and adapting during the internship program. This finding emphasizes the importance of strengthening growth mindset as a strategy, which can be supported through counseling services, in improving student interns' self-efficacy.